Native cover crops enhance arthropod diversity in vineyards of the Cape Floristic Region - Michelle Eckert; Letodi L. Mathulwe; René Gaigher; Lize Joubert-van der Merwe; James S. Pryke (Journal of Insect Conservation, 2020)

Hypothalamic-pituitary-adrenal axis variants and childhood trauma influence anxiety sensitivity in South African adolescents - Jacqueline S. Womersley; Lindi I. Martin; Lize van der Merwe; Soraya Seedat; Sian M. J. Hemmings (Metabolic Brain Disease, 2018)

Curcumin Rescues a PINK1 Knock Down SH-SY5Y Cellular Model of Parkinson’s Disease from Mitochondrial Dysfunction and Cell Death - Celia van der Merwe; Hayley Christy van Dyk; Lize Engelbrecht; Francois Hendrikus van der Westhuizen; Craig Kinnear; Ben Loos; Soraya Bardien (Molecular Neurobiology, 2017)

Significance of dietary folate intake, homocysteine levels and MTHFR 677 C>T genotyping in South African patients diagnosed with depression: test development for clinical application - Darnielle Delport; Renata Schoeman; Nicole van der Merwe; Lize van der Merwe; Leslie R. Fisher; Dieter Geiger; Maritha J. Kotze (Metabolic Brain Disease, 2014)

The fat mass and obesity-associated FTO rs9939609 polymorphism is associated with elevated homocysteine levels in patients with multiple sclerosis screened for vascular risk factors - Wiliam Davis; Susan J. van Rensburg; Frans J. Cronje; Lindiwe Whati; Leslie R. Fisher; Lize van der Merwe; Dieter Geiger; M. Shafick Hassan; Tandi Matsha; Rajiv T. Erasmus; Maritha J. Kotze (Metabolic Brain Disease, 2014)

CYP2D6 genotyping and use of antidepressants in breast cancer patients: test development for clinical application - Nicole van der Merwe; Christianne S. H. Bouwens; Rika Pienaar; Lize van der Merwe; Yandiswa Y. Yako; Dieter H. Geiger; Maritha J. Kotze (Metabolic Brain Disease, 2012)
Approximately 25 % of clinically important drugs and numerous environmental carcinogens are metabolised by CYP2D6. Variation in the CYP2D6 gene and concomitant use of tamoxifen (TAM) with certain antidepressants may increase recurrence risk in breast cancer patients due to reduced enzyme activity. In this study we determined the appropriateness of adding CYP2D6 genotyping to the breast cancer genetic testing options already available in South Africa, which include BRCA mutation screening and transcriptional profiling to assess estrogen receptor (ER) status. A total of 114 South African breast cancer patients, including 52 Caucasian and 62 Coloured (Mixed ancestry), and 63 Caucasian control individuals were genotyped for the most common inactivating allele (CYP2D6*4, rs3892097) previously identified in the CYP2D6 gene. In the initial validation data set consisting of 25 Caucasian and 62 Coloured patients, the CYP2D6*4 allele frequency was significantly higher in Caucasian compared to Coloured patients (24 % vs. 3 %, p < 0.001), similar to previous findings in the general South African population. Extended CYP2D6 genotyping was subsequently performed in an implementation data set of 27 Caucasian breast cancer patients, to determine the prevalence of depression and use of antidepressants in a clinical setting. A medical history of depression and/or use of antidepressants was reported in 37 % (10/27) of these breast cancer patients genotyped for CYP2D6*4. This translational research study has led to increased awareness among clinicians of the potential benefits of CYP2D6 genotyping to facilitate prevention of cumulative risk in a high-risk genetic subgroup of breast cancer patients considered for concomitant treatment of TAM and antidepressants that may reduce enzyme function.

Gene-gene interaction between tuberculosis candidate genes in a South African population - Erika de Wit; Lize van der Merwe; Paul D. van Helden; Eileen G. Hoal (Mammalian Genome, 2011)

Genetic variation in angiotensin-converting enzyme 2 gene is associated with extent of left ventricular hypertrophy in hypertrophic cardiomyopathy - Lize van der Merwe; Ruben Cloete; Miriam Revera; Marshall Heradien; Althea Goosen; Valerie A. Corfield; Paul A. Brink; Johanna C. Moolman-Smook (Human Genetics, 2008)

A linkage and family-based association analysis of a potential neurocognitive endophenotype of bipolar disorder - Jonathan Savitz; Lize van der Merwe; Mark Solms; Rajkumar Ramesar (NeuroMolecular Medicine, 2007)

A linkage and family-based association analysis of a potential neurocognitive endophenotype of bipolar disorder - Jonathan Savitz; Lize Merwe; Mark Solms; Rajkumar Ramesar (NeuroMolecular Medicine, 2007)